Case report: Resection of a massive primary sacrococcygeal mature teratoma in an adult using 3-dimensional reconstruction and mixed reality technology - Zhang, He; Ji, Lu; Liu, Jinxin; Li, Shizhe; Chen, Ting; Li, Jiatong; Shang, Guanning (Frontiers in Surgery, 2022)
INTRODUCTION: Teratomas are rare neoplasms that arise from pluripotent germ cells. Sacrococcygeal teratomas are often diagnosed in infants but are rare in adults; a mature teratoma can contain hair, teeth, bony tissue, and other mature tissue types. Herein, we report for the first time a patient with a teratoma containing intact bones that formed a pseudoarthrosis. CASE REPORT: A 49-year-old woman was admitted to hospital after a massive life-long sciatic tumor had begun to grow larger over the past year. A 16 × 25-cm solid mass with a clear boundary was palpable in the sacrococcygeal region. Radiography, computed tomography, and magnetic resonance imaging indicated a sacrococcygeal teratoma, although blood alpha-fetoprotein levels were normal. The teratoma was completely excised using 3-dimensional reconstruction mixed reality (MR) technology with no notable complications. Postoperative pathological examination of the excised lesion confirmed a mature teratoma. Interestingly, two intact irregular bones that formed a pseudoarthrosis were isolated; one was 11 cm and the other 6 cm. The patient is currently healthy and has experienced no recurrences. CONCLUSION: Sacrococcygeal teratomas are rare, especially in adults, and often comprised lots of components, such as fat, bony tissue. However, it’s first reported that formation of pseudoarthrosis in this case so far. It is difficult for surgeons to achieve complete excision without complications owing to the complex anatomic structure of the sacrum. The 3-dimensional reconstruction and MR technology based on computed tomography can provide spatial visualization, which allows surgeons to examine the teratoma at different angles preoperatively. Combining 3-dimensional reconstruction and MR technology in this case can improve the rates of complete sacrococcygeal teratoma resection and diminish recurrences.